Absorption and lymphatic transport of cholesterol and sitosterol in the rat - Christer Sylvén; Bengt Borgström (Journal of Lipid Research, 1969)
An attempt was made to determine the mechanism for the greater absorbability of cholesterol as compared to sitosterol.Sitosterol-22,23-3H in different combinations with cholesterol-4-14C, dissolved in 0.8 ml of triolein, was fed to rats with lymph fistulae. Feeding 1.5, 50, or 100 μmoles of sitosterol resulted in a transfer to the lymph in 24 hr of 3-6% of the sitosterol, largely independent of the dose fed. The total amount of sitosterol transferred to the lymph was therefore almost linearly related to the dose fed. 30% of a tracer dose of cholesterol-4-14C fed together with the sitosterol was transferred to the lymph in 24 hr.When a total of 50 μmoles of sterol, containing cholesterol-14C and sitosterol-3H in the proportions 1 : 3, 1 : 1, and 3: 1, was similarly fed, we found that sitosterol had no significant effect on the lymphatic transport of the simultaneously fed cholesterol.The ratio of 3H to 14C in the lymph was between 0.1 and 0.2 (the ratio in each fed mixture being taken as 1.0). The ratio was constant during the absorption period and independent of the ratio of sterols in the fed sterol mixture. Thus the same percentage of each sterol was always absorbed, and the sterols exerted no mutual interference in each others' absorption.We conclude that the mechanism for specificity in sterol absorption must be located early in the transport of the sterols within the intestinal mucosa cell.